Too Many Cooks Spoil the Broth – Variable Potencies of Oxidizing Mn Complexes of a Hexadentate Carboxylato Ligand. Issue 21 (29th April 2015) - Deville, Claire; Finsel, Maik; de Sousa, David P.; Szafranowska, Barbara; Behnken, Julian; Svane, Simon; Bond, Andrew D.; Seidler‐Egdal, Rune Kirk; McKenzie, Christine J.
Abstract: Given the hexadenticity of the monoanionic ligand in the procatalyst [Mn(tpena)(H2 O)](ClO4 ) tpena – = N, N, N′ ‐tris(2‐pyridylmethyl)ethylenediamine‐ N′ ‐acetate, it is perhaps surprising that this complex can catalyze the epoxidation of alkenes. When peracetic acid is used as terminal oxidant, the selectivity and rates of reactions are comparable with those reported for the manganese complexes of the commonly employed neutral tetradentate N4 ligands under analogous conditions. Cyclooctene conversion rates are similar when tert ‐butyl hydroperoxide (TBHP) is used; however, the selectivity is greatly diminished. In the absence of organic substrates, [Mn II (tpena)] + catalyzes water oxidation by TBHP (initial rate ca. 23 mmol/h when [Mn] = 0.1 mM, at room temp.). To explain the variations in the selectivity of catalytic epoxidations and the observation of competing water oxidation, we propose that several metal‐based oxidants (the "cooks") can be generated from [Mn II (tpena)] + . These embody different potencies. The most powerful, and hence least selective, is proposed to be the isobaric isomer of [Mn IV 2 (O)2 (tpena)2 ] 2+, namely an oxylic radical complex, [(tpena)Mn III (μ2 ‐O)Mn IV (O · )(tpena)] 2+ . The formation of this species depends on the catalyst concentration, and it is favoured when TBHP is used as the terminal oxidant. The generation of the less potent [Mn IV (O)(tpena)] +, which we propose as the direct oxidant in epoxidation reactions, is favoured in non‐aqueous solutions when peracetic acid is used as the terminal oxidant. Abstract : A manganese(II) complex of a hexadentate ligand catalyzes epoxidation. However, reaction conditions are critical since several metal‐based oxidants with varying potencies can be generated. This observation is probably general for related catalysts, and consequences include decreased selectivity and competing water oxidation.